Analisis Tekanan Air Pori Dan Rembesan Pada Proyek Pembangunan Bendungan Tigadihaji Sumatera Selatan - Reymond Martin Sutrisno Panggabean; Wikan Kresno Sadono (Racic : Rab Construction Research, 2025)
A problem often encountered in the construction of an embankment dam is seepage. Basically, water stored in a reservoir or dam will always find a way out from upstream to downstream through porous soil in the body of the dam. Seepage will become a big problem if the grains of embankment material in the body of the dam are also eroded by the flow of water. The erosion of the grains of material in the dam body can cause piping which can lead to dam collapse. To avoid dam collapse caused by seepage, the dam must be designed to be safe against seepage. Material selection and embankment compaction need to be considered so that the embankment soil layer does not produce excess pore water pressure. In this case study, we will model the pore water pressure at elevation +243.5 or the crest of the dam body and calculate the seepage discharge based on the material to be used as embankment material at Tigadihaji Dam. The water level to be used in this modeling uses the normal water level at elevation +235.5 and the flood water level at elevation +240.45 according to the shop drawings. This modeling will use the help of Geostudio Seep/W Version 2012 software.